Theological and religious exploration of an Indian indentured descendant: Dr Betty Govinden - Archary, Kogielam K. (Verbum et ecclesia, 2025)
This article reflects on and records significant aspects of the life of the 80-year-old Dr Devarakshanam (Betty) Govinden. Emphases of this research are on the last 50 years, focusing on her life in terms of religion, particularly her theological contribution to South African society, especially through the Circle of Concerned African Women Theologians. In terms of religious heritage, Govinden was born a Christian of indentured Indian ancestry. This study provides insights, knowledge, and information on 50 years of church orthodoxy in South Africa from the perspective of an Indian female theologian, focusing on the interdisciplinary field of Christianity, theology, and religion. Information was gathered through one-on-one, semi-structured interviews with Dr Govinden, exploring her theological and religious journey as a descendant of Indian indentured labourers. Key themes included: (1) her experiences from early childhood, adolescence, and student life; (2) the influence of her parents; (3) her path to becoming a theologian and significant moments in her life as both a Christian and theologian; and (4) her perspective on the South African community as a religious community over the past 50 years. Additionally, select publications of Govinden were used as sources to gain insights on her views on the church. Analysis of the information gathered was conducted in an unmediated manner, and relevant themes emerged. Intradisciplinary and/or interdisciplinary implications: The research contributes to the body of knowledge and information on 50 years of church orthodoxy in South Africa, with the aim of presenting the research results with a focus on Christian theology and religion. This research uses the role and contribution of Dr Devarakshanam (Betty) Govinden, an Indian indentured labourer descendant, as a framework for analysis and discussion.